APLICAÇÃO DE ARGILA MARANHENSE COMO ADSORVENTE PARA OS CORANTES TEXTEIS VIOLETA CRISTAL E AZUL TURQUESA EM SISTEMA AQUOSO - Ferreira, Railson da Cunha (2014)
The adsorption is widely used for the treatment of textile effluents and with the high cost of conventional adsorbents search becoming more alternative adsorbents, efficient and cheaper. The maranhense clay treated with inorganic acid, in this study of hydrochloric acid, was applied to the removal of textile dyes crystal violet (CV) and turquoise blue (TB). We investigated the adsorptive effect of parameters such pH, temperature, concentration of dyes and contact time in the adsorption process as the kinetic, and thermodynamic parameters of isothermal adsorption. The adsorbent was characterized by analysis in the infrared (IR), X-ray diffraction (XRD), point of zero charge (PZC) and chemical composition analysis by X-ray fluorescence (XRF). The kinetic data were best represented by the kinetic model of pseudosecond order and the adsorption isotherms by the Sips isotherm model. The maximum adsorption capacity of the treated clay was 103.02 mg gˉ¹ for crystal violet and 97.91 mg gˉ¹for the turquoise blue. The thermodynamic parameters showed that the adsorption process is endothermic (ΔHºads positive), spontaneous and favorable (ΔG°ads negative) and also presented randomness of the system (ΔS⁰ads positive). The maranhense treated clay proved to be a good adsorbent for low cost, easy to purchase and can be used in the adsorption process.